1996
DOI: 10.1136/vr.138.21.520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a commercial gE blocking ELISA test for detection of antibodies to infectious bovine rhinotracheitis virus

Abstract: Veterinarv Record (1996) 138, 520 INACTIVATED and attenuated gE deleted bovine herpesvirus type 1 (Hv-1) marker vaccines are now available in most European countries (Kaashoek and others 1994, 1995). These vaccines are suitable for reducing BHV-1 transmission and could be used in control or eradication programmes in infected countries. A commercial anti-BHV-1 gE blocking ELISA test kit is used to differentiate between immunised and naturally infected BHV-1 cattle. This study was undertaken to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Indeed the strength of the tool is fully dependent on the capacity of the diagnostic test at detecting BoHV-1 gE specific antibody. But the sensitivity of the only available gE specific ELISA is around 70% [97,160]. This rather low level of sensitivity is responsible for 30% false negative answers at individual tests but it remains sufficient to guarantee a high sensitivity at the level of infected herds.…”
Section: The Diva Strategy (Aiming At Differentiating Infected From Vmentioning
confidence: 99%
“…Indeed the strength of the tool is fully dependent on the capacity of the diagnostic test at detecting BoHV-1 gE specific antibody. But the sensitivity of the only available gE specific ELISA is around 70% [97,160]. This rather low level of sensitivity is responsible for 30% false negative answers at individual tests but it remains sufficient to guarantee a high sensitivity at the level of infected herds.…”
Section: The Diva Strategy (Aiming At Differentiating Infected From Vmentioning
confidence: 99%
“…Enhanced culling of seropositive animals and purchase restrictions are more appropriate measures in order to rapidly achieve the seronegativity of the entire stock. Moreover, the lower sensitivity of gE.ELISA in comparison with other ELISAs and the 24 h virus neutralization test (Perrin et al, 1996;De Wit et al, 1998;Hage et al, 1998;Wellenberg et al, 1998) should be mentioned; fully seronegative cattle therefore offer a greater guarantee of freedom from disease than those immunized with gE-deleted vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that serum samples with low VNT titers (Յ8) could be negative in both gE ELISA systems. Perrin et al (17) also showed that serum samples with low VNT titers can give negative results in the gE-blocking ELISA. The results of the detection limit for serum (Table 2) underline these published data and indicate that in both gE ELISA systems the titers in serum are lower than the VNT titers in serum.…”
Section: Discussionmentioning
confidence: 99%